MARKETING KNOWLEDGE MANAGEMENT STRATEGY FOR IMPROVING ORGANIZATIONAL PERFORMANCE AND COMPETITIVENESS - “AN APPLIED STUDY ON PRIVATE AND PUBLIC HOSPITALS IN JEDDAH CITY” - Saaty, Abdalelah S. (European Scientific Journal, ESJ, 2014)
Purpose - This study aims at highlighting the significance and importance of utilizing Knowledge Management (KM) and its role for translating research and evidence into policy, practice and social transformation. Design-methodology-approach- The study shows the roles of knowledge management (KM) and its’ practices in improving organizational performance and competitiveness. The empirical research method was evaluated by specialized experts, conducted by means of questionnaires. Correlation analyses were employed to test the validity of the procedure. Findings- The findings of the study confirmed positive relationships between the level of utilizing and adopting “Knowledge Management” and the success of an organizational performance and competitiveness. Originality/value– The study will focus on a few straightforward and practical KM tools and techniques designed to help organizations and individuals, to get “the right knowledge, in the right place, at the right time,” particularly in influencing an action or a decision, for improving organizational performance and competitiveness.